ANALISIS TINGKAT KEPUASAN PEMUSTAKA TERHADAP LAYANAN DI PERPUSTAKAAN BALAI ARKEOLOGI DAERAH ISTIMEWA YOGYAKARTA DENGAN METODE LIBQUAL +TM - Indra Saputro, Bayu; Timur Utami, Puspitaningrum (BACA: Jurnal Dokumentasi dan Informasi, 2020)
The purpose of this study was to determine the satisfaction of users of the quality of service in the Balai Arkeologi Daerah Istimewa Yogyakarta library using the LibQUAL+TM, in this method there are four indicators namely affect service, library as place, personal control, and information access. The research method used in this study is to use quantitative methods. The population in this study is the visitors who come to the library from April to December 2018. The sample used in this study amounted to 50 respondents. Gap analysis shows that the overall dimensions of LibQUAL+TM are negative. So there is a need for corrective actions to meet the user’s expectations. By using importance-performance analysis, it was found that subvariable personal control on modern equipment items (items 20) had a gap of -0.76. The user assumed that the photocopy machine facilities and infrastructure were needed by the user, but in fact the photo copy service was not provided by the library. Whereas the value of the User Satisfaction Index at the Balai Arkeologi Daerah Istimewa Yogyakarta library shows a number of 87.43%, which indicates the user satisfaction index is satisfied with the performance of library services.